2023
DOI: 10.1039/d2nh00520d
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the improved stability of amorphous boron-nitride upon carbon doping

Abstract: We report on a large improvement of the thermal stability and mechanical properties of amorphous boron-nitride upon carbon doping. By generating versatile force fields using first principles and machine learning...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…However, larger H doping worsens the mechanical properties due to fewer sp 3 -hybridized atoms, lower density, and more porous structure. Reduction in mechanical properties with lower density and sp 3 -hybridized atoms has already been shown for α-BN and other amorphous structures [9,10,[34][35][36]. Even though the reported Young's modulus values in this study are lower than hexagonal and cubic BN, α-BN:H still has superior mechanical properties than other ultralow-dielectric materials.…”
Section: Mechanical Properties Of α-Bn:hsupporting
confidence: 47%
See 3 more Smart Citations
“…However, larger H doping worsens the mechanical properties due to fewer sp 3 -hybridized atoms, lower density, and more porous structure. Reduction in mechanical properties with lower density and sp 3 -hybridized atoms has already been shown for α-BN and other amorphous structures [9,10,[34][35][36]. Even though the reported Young's modulus values in this study are lower than hexagonal and cubic BN, α-BN:H still has superior mechanical properties than other ultralow-dielectric materials.…”
Section: Mechanical Properties Of α-Bn:hsupporting
confidence: 47%
“…However, at larger concentrations, H atoms disrupt the stability of the α-BN samples. Kaya et al [10] showed that the thermal stability of C-doped α-BN samples can be improved with larger amounts of sp 3 -hybridized atoms. Similarly, Cloutier et al [31] and Liu et al [32] showed that increasing the density of α-C films and number of sp 3 -hybridized atoms can improve the stability of films.…”
Section: Thermal Stability Of α-Bn:hmentioning
confidence: 99%
See 2 more Smart Citations
“…A stable MLIP with an improved accuracy and stability can then be refitted using the second training dataset. This two-step passive training approach has recently been successfully applied in several studies for predicting the uniaxial stress-strain and failure responses of 2D materials 4,44,[47][48][49][50] and amorphous systems 51 and showed outstanding accuracy as compared with DFT results. The two-step passive training approach can substantially facilitate the development of MLIPs, but the stability is not guaranteed and thus the necessity of on-the-fly or active learning cannot be completely omitted.…”
Section: Training a Mlip For The Analysis Of Mechanical Propertiesmentioning
confidence: 99%